2022
DOI: 10.1007/s00603-022-03030-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mode I Fracture Toughness of Shale Specimens by Different Fracture Theories Considering Size Effect

Abstract: In this study, mode I fracture tests on cracked straight-through Brazilian disc (CSTBD) and notched semi-circular bend (NSCB) shale specimens with different sizes were conducted to investigate the difference between maximum tangential stress fracture criterion and the size effect law (SEL) model in predicting apparent fracture toughness (Ka) of shale. In addition, the effects of specimen size and geometry on the Ka and the selection of fracture criterion on the prediction of the inherent fracture toughness (KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This indicates that the distribution of tangential stresses at the crack tip front in the two specimen configurations studied in this research is independent of the specimen's configuration. Previous studies [7] have shown that when the specimen dimensions are sufficiently large or the ligament length is sufficiently long, the tangential stress at the crack tip front can be completely determined based on the stress intensity factor alone. Both configurations in this study satisfy this condition.…”
Section: Initial Fracture Toughness and Unstable Fracture Toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the distribution of tangential stresses at the crack tip front in the two specimen configurations studied in this research is independent of the specimen's configuration. Previous studies [7] have shown that when the specimen dimensions are sufficiently large or the ligament length is sufficiently long, the tangential stress at the crack tip front can be completely determined based on the stress intensity factor alone. Both configurations in this study satisfy this condition.…”
Section: Initial Fracture Toughness and Unstable Fracture Toughnessmentioning
confidence: 99%
“…It is worth noting that these testing methods do not yield consistent fracture toughness results, and different fracture toughness testing methods produce significantly different results [6]. Many studies have indicated that this disparity may be attributed to the presence of a fracture process zone at the crack tip front in rock specimens [7,8].…”
Section: Introductionmentioning
confidence: 99%